Sources on Georgians in the Holy Land: The Publication of the Syriac "Life of Peter the Iberian" in English Translation - Cornelia Horn,; Robert R. Phenix Jr., (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2014)
The main part of the book features the ancient biography of the Georgian hero Peter the Iberian, who was born in 413 or 417 CE into the royal family of the Iberian kingdom in the region that is now the eastern part of Georgia. Over the course of his life, Peter distinguished himself as a pilgrim, monk, bishop, and leader of anti-Chalcedonian Christians in Palestine.